Correlation between Media Exposure, Communication Intensity with Health Experts, Perceived Susceptibilty, and Behavioral Intention of Pregnant Women to Perform HIV Testing in Semarang - Intan Amanda; Dra. Sri Widowati Herieningsih, MS (Interaksi Online, 2016)
Many of HIV cases has happened in Semarang and it becomes the background of this research. The problem that appears is the low intention of pregnant women to perform HIV testing. The purpose of this study is to determine the correlation between media exposure, communication intensity with health experts, perceived susceptibilty, and behavioral intention of pregnant women in Semarang to perform HIV testing. The concept of selective exposure, a reference group theory and the theory of health belief model are used to explain the relationship/correlations between media exposure, the communication intensity with the health experts, perceived susceptibilty, and behavioral intention of pregnant women to perform HIV testing in Semarang. This study uses the non-probability sampling with incidental sampling technique. The population in this study is the pregnant women in Semarang, who have gotten the media exposure regarding information about HIV, with 60 respondents become the sample. Pearson correlation test analysis is used to test the hypothesis.The variable of media exposure does not significantly correlate with the behavioral intention of pregnant women in Semarang to perform HIV testing, because the significance value shows p=0.147 (p>0.05). The communication intensity with the health experts variable positively corelates with the behavioral intention of pregnant women in Semarang to perform HIV testing, because the significance value shows p=0.025 (<0.05). The correlation value of 0.290 indicates a weak correlation between the two variables. The variable of perceived susceptibilty positively correlates with a variable interest test for HIV in pregnant women in the city, because the significance value shows p=0.002 (<0.05). The correlation value of 0.391 indicates a weak correlation between the two variables.Advice given in accordance to results of research suggests health experts to take the initiative to increase the communication intensity with pregnant women, as well as to provide information and give more intensive persuasion to pregnant women on the importance of HIV testing.